Teoria do reexame compulsório do provimento jurisdicional sob o viés de uma Filosofia do Direito Processual e à égide do Estado de Direito Democrático - Teixeira, Denilson Victor Machado (2014)
The mandatory degree of jurisdiction, derived from the Lusitanian right (mid-fourteenth century), under the influence of the inquisitorial process, emerged as a Brazilian legal institute of the Civil Procedure, within the article 90 of the Law of October 4, 1831, establishing it as an appeal (ex officio appeal), so that the magistrate interposed it from his own judgment against the National Treasury. So, ontologically, the mandatory double degree of jurisdiction must exist due to the Public Administration, despite the purpose is the collective defense of the public interest (not state). Currently, due to changes determined by the Federal Statutory Law n. 10.352, of December 26, 2001, the current article 475 of the Code of Civil Procedure provides the submission to the double jurisdiction, producing no effect until confirmed by the court after the judgment against the Union, Member States, the Federal District, the Municipalities, and respective agencies and foundations governed by the Public Law. Moreover, it is conceptualized as a condition of providing compulsory rejudgement to the the first instance by the higher order to produce its legal and juridical effects definitively as soon occurs the res judicata of decisum. In foreign legislation such institute is applied in few countries of Hispanic America, under the name of consultation. Under the aspect of Legal Sociology, the mandatory double degree of jurisdiction is effective, because the rule of law (art. 475 of the Code of Civil Procedure) is being fulfilled by their recipients. However, the necessary remittance is characterized as a procedural privilege, and analyzed from the standpoint of constitutional equality (art. 5, caput, first part, and inc. XXXVII, CRFB/1988) generates an apparent antinomy of legal norms, in such a way that applied hierarchical criterion, and, consequently, it turns invalid alluded art. 475 of the Code of Civil Procedure, well known as an unconstitutional Democratic Rule of Law. Concerning Legal Philosophy, adding up the value of justice to the equality, by the way, in obedience to the constitutional preamble parental 1988, it is clear that the mandatory jurisdiction is unfair because, in strictly procedural context, the parts must obtain isonomic treatment by State Judge, by impartial nature. Therefore, it becomes stale that the State Administration may not enjoy such a privileged position in the procedural field, even as it is properly harnessed legal and institutionally, and on the other hand, the born defender of the collective interest is the Prosecutor, as it is adduced in the art. 127, caput, CRFB/1988, where it is pondered the Ministerial participation to resolve the dispute. Anyway, in our times, the Civil Procedure must be grounded in effectiveness (art. 5, inc . LXXVIII, CRFB/1988) and equality, while this as instrumental justice (value), and in order to congratulate the procedural good faith